2020
DOI: 10.4028/www.scientific.net/kem.859.239
|View full text |Cite
|
Sign up to set email alerts
|

Development of Electrospun Shellac and Hydroxypropyl Cellulose Blended Nanofibers for Drug Carrier Application

Abstract: The aim of this study was to develop the electrospun shellac (SHL) and hydroxypropyl cellulose (HPC) blended nanofibers for drug carrier application. The effects of polymer solution and electrospinning parameters, including SHL-HPC ratio, HPC concentration, applied voltage and flow rate, on the appearance of fibers were investigated. Based on the results, electrospun fiber was not obtained when a solution of HPC alone was employed. However, the fibers would be obviously fabricated as SHL was added to the HPC s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, the release of active compounds might well be altered regardless of the type of polymer used to fabricate electrospun fibers. Due to the mechanical properties, controlled degradation rate, and biological compatibility of shellac, a natural polymer derived from the excretions of the lac Kerria lacca insect, electrospun fibers seemed to become widely attractive [ 13 , 14 , 15 , 16 , 17 ]. Shellac resin contains derivatives of jalaric and laccijalaric acids ( Figure 2 ), and a detailed analysis of the compounds in shellac was recently revealed by flow injection and liquid chromatography coupled with electrospray ionization and mass spectrometry [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the release of active compounds might well be altered regardless of the type of polymer used to fabricate electrospun fibers. Due to the mechanical properties, controlled degradation rate, and biological compatibility of shellac, a natural polymer derived from the excretions of the lac Kerria lacca insect, electrospun fibers seemed to become widely attractive [ 13 , 14 , 15 , 16 , 17 ]. Shellac resin contains derivatives of jalaric and laccijalaric acids ( Figure 2 ), and a detailed analysis of the compounds in shellac was recently revealed by flow injection and liquid chromatography coupled with electrospray ionization and mass spectrometry [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that an excess of electrostatic forces may cause the polymer flow to undergo overstretching, thereby producing fibers with larger diameters [62,63]. Although certain studies have reported no correlation between the voltage applied and the diameter of the fibers [64], it was discovered that increasing the voltage during the electrospinning process generated more charges, which improved the polymer solution's ability to stretch and contributed to the production of thinner nanofibers with a smaller diameter [65]. These results are consistent with those of other investigations [23,66,67] that have documented comparable results.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the mechanical characteristics, controlled biodegradation, and biological compatibility of shellac, electrospun fibers made from shellac, a natural polymer derived from the insect Kerria lacca ’s secretion, appear to be gaining widespread popularity [ 126 , 127 , 128 , 129 , 130 , 131 , 132 ]. Consequently, this article explores the creation of bioactive shellac electrospun fibers.…”
Section: Electrospinningmentioning
confidence: 99%